2020
DOI: 10.1371/journal.pone.0231088
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between mindfulness, depression, stress and academic performance in medical students: A Saudi perspective

Abstract: There is a growing body of research that shows a significant association between mindfulness and mental health. However, studies on Saudi populations are still in their infancy. Mindfulness is a personal tendency to focus on the present time in a non-judgmental manner, including the interior and exterior experience of feelings and events. The first aim of this study is to examine the relationship between mindfulness, stress, depression, and academic performance in a sample of medical students from King Saud Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
4
22
1
8
Order By: Relevance
“…Firstly, mindfulness and perceived stress showed a significant negative correlation. This is in line with previous studies [ 9 , 12 , 13 , 25 ] and serves to confirm the validity of both parameters. Secondly, students progressing from their first to their second year at medical school perceived increasing stress and again, this has previously and internationally been reported [ 5 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Firstly, mindfulness and perceived stress showed a significant negative correlation. This is in line with previous studies [ 9 , 12 , 13 , 25 ] and serves to confirm the validity of both parameters. Secondly, students progressing from their first to their second year at medical school perceived increasing stress and again, this has previously and internationally been reported [ 5 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the lack of any correlation between mindfulness and academic achievements – assessed twice at T1 and T3 - was unexpected. Even though our findings confirm a previous cross sectional study on 289 medical students across all academic years, results from middle school children and a broad variety of bachelor students were more promising [ 12 , 22 ]. However, the latter study relied on self-reported grade point averages and did not report on any time delay between exam and assessment of mindfulness [ 22 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Literature suggests that mindfulness is associated with an attitude of acceptance (Bishop et al, 2004). Thus, individuals with high levels of mindfulness are less likely to be overwhelmed by the distressing feelings such as depression (e.g., Alzahrani et al, 2020;Barnes& Lynn, 2010;Carmody & Baer, 2008;Fisak & Von Lehe, 2012;Royuela-Colomer & Calvete, 2016) and anxiety (MacDonald & Olsen, 2020;Singh et al, 2020). In support, an immense number of studies documented that mindfulness programs decreased individuals' levels of depression (Zemestani&Nikoo, 2019) and anxiety symptoms (e.g., La Torre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%